The role of achievement goal orientations in the relationships between high school students’ anxiety, self-efficacy, and perceived use of revision strategies in argumentative writing - Paul, Narmada; Lin, Tzu-Jung; Ha, Seung Yon; Chen, Jing; Newell, George E. (Journal of Writing Research, 2021)
This study examined the relationships between writing anxiety, writing self-efficacy, and perceived use of revision strategies in high school students with different achievement goals as they learned argumentative writing in English Language Arts classrooms. Three achievement goal orientation profiles emerged from a sample of 307 American high school students on the basis of their mastery, performance-approach, and performance-avoidance goal orientations: Low on All, Average on All, and High on All. These three profiles of students significantly differed with respect to their writing anxiety and their perceived use of revision strategies. Writing self-efficacy mediated the effect of writing anxiety on the perceived use of revision strategies for students in the Average on All profile only. The findings suggest that students are diverse in their motivational and affective experiences with respect to argumentative writing, and caution against using a one-size-fits-all approach for teaching argumentative writing to students.